1982
DOI: 10.1002/col.5080070204
|View full text |Cite
|
Sign up to set email alerts
|

A new colour‐perception lantern

Abstract: A new colour‐perception lantern shows red, green, and white lights which are within current international chromaticity limits for signal lights in all forms of transport, at three levels of luminous intensity. The light source, filters, and power supply have long‐life characteristics and the whole lantern is intended to be maintenance‐free. The operator's functions are simple and clear, and a fixed routine is proposed for the colour‐perception test. There are two models, Type A approved for the British Armed S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…It was developed to replace the Board of Trade lantern after an inquiry on vision standards iqmaritime occupations.177 There are two versions (A and B) 178 Path Indicator (PAPI) used in airports. Tanabe and associatersls6 used red, yellow and yellow-green LEDs.…”
Section: Holmeswright Lantern (H-w)mentioning
confidence: 99%
“…It was developed to replace the Board of Trade lantern after an inquiry on vision standards iqmaritime occupations.177 There are two versions (A and B) 178 Path Indicator (PAPI) used in airports. Tanabe and associatersls6 used red, yellow and yellow-green LEDs.…”
Section: Holmeswright Lantern (H-w)mentioning
confidence: 99%
“…6 A, as derived independently by three groups [27] from fibre X-ray scattering measurements (see Fig. 5 , a ) .…”
Section: Bmer 3a L6mer 4d 16mer 4a (Fully Deprotected)mentioning
confidence: 99%
“…They are used by microorganisms as a means to store energy and reductase equivalents and as a carbon source (high-molecular-weight s-P(3-HB), > lo5 Dalton). A copolymer of P(3-HB) and P(3-HV) (V = valerate) is produced by fermentation and sold as a biodegradable and biocompatible plastic material under the trade name BZOPOL [6]. Low-molecular-weight P(3-HB) (100-200 units) was found in the membranes of prokaryotic and eukaryotic cells.…”
mentioning
confidence: 99%
“…Ruland (15) and Vonk (16) have shown that deviations from ideal Porod-type behaviour for lamellar structures alter this behaviour such that for the sharp boundary model and for the (three-phase) diffuse interface model, where K, is proportional to the electron density difference between phases and 0 is an indication of the interface thickness in eq. [2] and of the density fluctuations within phases in eq.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
“…Poly(P-hydroxybutyrate), PHB, and its random copolymers with 3-hydroxyvalerate, P(3HB-co-3HV) are bacterially produced biodegradable thermoplastics (1)(2)(3). They have found a market niche as biodegradable packaging materials and surgical implants due, in part, to properties imparted by their unique crystallization behaviour (4,5).…”
Section: Introductionmentioning
confidence: 99%